2023
DOI: 10.3389/fnins.2023.1145923
|View full text |Cite
|
Sign up to set email alerts
|

Neuronally enriched microvesicle RNAs are differentially expressed in the serums of Parkinson’s patients

Abstract: BackgroundCirculating small RNAs (smRNAs) originate from diverse tissues and organs. Previous studies investigating smRNAs as potential biomarkers for Parkinson’s disease (PD) have yielded inconsistent results. We investigated whether smRNA profiles from neuronally-enriched serum exosomes and microvesicles are altered in PD patients and discriminate PD subjects from controls.MethodsDemographic, clinical, and serum samples were obtained from 60 PD subjects and 40 age- and sex-matched controls. Exosomes and micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 120 publications
0
0
0
Order By: Relevance
“…There has been debate concerning the presence of L1CAM on the surface of EVs, given multiple processed forms of the protein and recent evidence showing that L1CAM is not associated with EV fractions from plasma and CSF ( Norman et al, 2021 ). Other groups that attempted to isolate L1CAM-positive EVs from plasma demonstrated that EVs indeed expressed L1CAM ( Dutta et al, 2021 , 2023 ; Gomes and Witwer, 2022 ; Aguilar et al, 2023 ). Thus, there is conflicting evidence regarding the presence of L1CAM on EVs and whether or not it can reliably be used as a marker of neuron-derived EVs ( Gomes and Witwer, 2022 ).…”
Section: Cns Cell-derived Exosomes As Biomarkers Of Neurodegenerative...mentioning
confidence: 99%
See 2 more Smart Citations
“…There has been debate concerning the presence of L1CAM on the surface of EVs, given multiple processed forms of the protein and recent evidence showing that L1CAM is not associated with EV fractions from plasma and CSF ( Norman et al, 2021 ). Other groups that attempted to isolate L1CAM-positive EVs from plasma demonstrated that EVs indeed expressed L1CAM ( Dutta et al, 2021 , 2023 ; Gomes and Witwer, 2022 ; Aguilar et al, 2023 ). Thus, there is conflicting evidence regarding the presence of L1CAM on EVs and whether or not it can reliably be used as a marker of neuron-derived EVs ( Gomes and Witwer, 2022 ).…”
Section: Cns Cell-derived Exosomes As Biomarkers Of Neurodegenerative...mentioning
confidence: 99%
“…The RNA content of neuron-derived EVs has also been under investigation. Of note, while there is a wealth of studies measuring RNA in total EVs from the blood of patients with neurodegenerative diseases, as discussed elsewhere ( Liu et al, 2019 , 2022 ; Sproviero et al, 2022 ; Bagyinszky et al, 2023 ; Dutta et al, 2023 ; Xu et al, 2024 ), there are fewer studies for neuronal and other CNS-derived EVs ( Cha et al, 2019 ; Banack et al, 2020 , 2022 ; Serpente et al, 2020 ; Zou et al, 2020 ; Durur et al, 2022 ; Li et al, 2022a , b ; Pounders et al, 2022 ; Aguilar et al, 2023 ; Dunlop et al, 2023 ). This likely reflects poor reproducibility of RNA findings from total plasma, serum and CSF EVs due to unstandardized EV isolation techniques, use of different downstream RNA measurement techniques and variations in the patient populations studied ( Liu et al, 2022 ; Dutta et al, 2023 ).…”
Section: Cns Cell-derived Exosomes As Biomarkers Of Neurodegenerative...mentioning
confidence: 99%
See 1 more Smart Citation